Nourishing the Land, Nourishing the People : the Story of one Rural Development Project in the Deep South of Madagascar that made a Difference - Shapiro, Brett (CABI, 2014)
This book covers a two-year period and brings together the efforts of a team that was established and coordinated by Benoît Thierry, who was responsible for the IFAD project. The collective work of drafting and editing, which was led by Brett Shapiro with the support of Assefa Woldeyes and Harifidy Ramilison, was also supported “on the ground” by Andrianiainasoa Rakotondratsima, the Project Director. From 2006, project staff were encouraged to maintain all paper and electronic documentation (reports, analyses, databases, posters, photos and videos) in order to establish an electronic library of the project. The library can be accessed at www.phbm.mg, which contains all of the project’s activities since its inception, as well as at www.capfida.mg, which provides an analysis of the results of the project.